Creation and Evaluation of a Preoperative Education Website for Hip and Knee Replacement Patients—A Pilot Study - Dayucos, Amelia (Medicina (Kaunas), 2019)
Background and Objectives: There is limited research on the question of whether web-based preoperative education can improve surgical patient outcomes. The purpose of this pilot study was to determine the usability, utility, and feasibility of a website created to increase engagement and improve the quality of the preoperative education that patients having hip and knee arthroplasty surgery receive. Materials and Methods: A website was created, and its appearance was designed with evidence-based “menu-driven” drop-downs to make the screen options age-appropriate to the patient population; the content was supported with video and PDFs of educational material, the same or similar to the usual education provided to patients. The patient-specific outcomes included qualitative data regarding patient knowledge, satisfaction, utilities, and usability. These objectives were assessed based on the perceived health website usability questionnaire online survey. Eighty patients who met inclusion criteria were recruited, ranging in age from 40 to 65 years old. Among them, 52.5% were female, 71.25% were scheduled for knee arthroplasty, and 28.75% hip arthroplasty. The patients were randomly assigned to the paper only or website education cohorts in a 50:50 ratio. However, only 19 from each cohort participated in the survey questionnaire. Results and Conclusions: We hypothesized that findings would show that patients receiving web-based education would feel more knowledgeable about their procedure, have less anxiety, and greater satisfaction with the addition of the website content; and that nurses would report that a website could conserve nursing time and resources. The study revealed no statistically significant differences between the cohorts, with an Alpha level set at 0.05. However, survey results showed that patients using the website rated self-perceived increase in knowledge, and their satisfaction in the time to find and review the information was higher than that of the paper-only cohort. The nursing survey revealed that website education improved workflow, efficiency, and patient education.